2011
DOI: 10.1021/ef2004943
|View full text |Cite
|
Sign up to set email alerts
|

Using Deep Eutectic Solvents Based on Methyl Triphenyl Phosphunium Bromide for the Removal of Glycerol from Palm-Oil-Based Biodiesel

Abstract: Biodiesel is a remarkable alternative to the decreasing resources for fossil fuels. One of the critical steps in producing biodiesel is its purification from the byproduct glycerol. The content of glycerol permissible must pass the EN 14214 and ASTM D6751 international biodiesel standards. In this work, methyl triphenyl phosphunium bromide as salt and three different hydrogenbond donors, namely, glycerol, ethylene glycol, and triethylene glycol, were selected to synthesize three deep eutectic solvents (DESs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(117 citation statements)
references
References 20 publications
(43 reference statements)
2
110
0
5
Order By: Relevance
“…4 Design for degradation Most of the components of DES are biodegradable [31] and as such do not persist in the environment for a longer period of time. For example, cholinium alkanoates based DESs are environmentally benign and biodegradable [32,33].…”
Section: Less Hazardous Constituents and Productsmentioning
confidence: 99%
“…4 Design for degradation Most of the components of DES are biodegradable [31] and as such do not persist in the environment for a longer period of time. For example, cholinium alkanoates based DESs are environmentally benign and biodegradable [32,33].…”
Section: Less Hazardous Constituents and Productsmentioning
confidence: 99%
“…Its advantages lie in mild conditions of the process performed at room temperature and atmospheric pressure. Some studies on vegetable oils have shown that the use of deep eutectic solvents (DESs) reduces the content of all impurities present in crude biodiesel [20][21][22]. Deep eutectic solvents are mixtures of two or three economically and environmentally acceptable components with a melting temperature lower than the melting temperature of individual components [23].…”
Section: Introductionmentioning
confidence: 99%
“…Among the DESs used, choline chloride seems to be the most common salt and ethylene glycol and glycerol are the most common hydrogen bond donors. Shahbaz et al used choline chloride with ethylene glycol and with 2,2,2-trifluracetamide in different molar ratios [20] while Ho et al used ternary deep eutectic solvents -choline chloride with both ethylene glycol and glycerol in different molar ratios [26]. Both papers report free glycerol removal and substantial total glycerol reduction for almost all experiments conducted.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to their potential as environment friendly solvents and advantages over conventional solvents and ionic liquids such as non-toxicity, non-reactivity with water and above all being biodegradable [1]. Moreover, they are synthesized easily in high purity at low cost in contrast to Ionic liquids which are very expensive and difficult to handle [2].…”
Section: Introductionmentioning
confidence: 99%
“…(3), density data are required. Since density data is unavailable in many cases, lately, we have reported an empirical group contribution method to predict densities of DESs [1]. In that method the critical properties of salt and HBD were estimated separately using the modified Lydersen-Joback-Reid method, while that of the mixture were calculated using Lee-Kesler equation.…”
Section: Introductionmentioning
confidence: 99%